Quaternary ammonium salt modified strong anion monolithic column
By grafting quaternary ammonium salt-based on epoxy resin-based monolithic column material, the problems of uneven pore distribution and non-specific adsorption in biological macromolecule separation in the prior art are solved, and efficient nucleic acid substance enrichment is achieved Set and separation effects.
Patent Information
- Application Number
- CN202411449265.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-05-10
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-17
AI Technical Summary
In the enrichment and separation of biological macromolecules, existing monolithic column materials have problems such as uneven pore distribution, nonspecific adsorption, poor toughness and complex process control, especially for poor separation of nucleic acid substances.
An epoxy resin-based monolithic column material is used and quaternary ammonium salt-based is grafted on its surface. Through hydroxylation and quaternary ammonium salt-based treatment, a pore structure with specific adsorption capacity is formed, which improves the ability to enrich nucleic acid substances.
It realizes the characteristics of uniform channel distribution, high flow rate and low operating pressure, and also has the specific adsorption capacity for nucleic acid substances, which improves separation purity and efficiency, and reduces process cycle and cost.
Smart Images

Figure BDA0005088597320000041 
Figure BDA0005088597320000042 
Figure BDA0005088597320000044
Abstract
Description
Technical Field
[0001] The present invention relates to a monolithic column material, and more specifically, to a monolithic column material for nucleic acid enrichment and separation. Background Art
[0002] At present, the separation and purification of biomolecules are basically achieved by modifying the surface ligands of chromatographic microsphere media to achieve separation and purification of different functions, so as to obtain relatively pure molecules as medicines, diagnostic reagents, biochemical process raw materials, food, cosmetic additives, etc. However, microsphere media as stationary phases have the following disadvantages: 1) The pore distribution is relatively small, and the separation ability for biomolecules with large molecular weight is poor; 2) The diffusion effect of chromatographic microspheres is obvious, and a long retention time is required to fully diffuse to the theoretical specific surface area of the microspheres, which takes longer for biomolecules; 3) The working pressure of the chromatographic column filled with microspheres is high, which is not conducive to the efficient operation of the system.
[0003] Monolith technology is a new generation of chromatographic stationary phase developed in recent years. It currently has obvious advantages over traditional porous microsphere filling media in the rapid separation and purification of biomacromolecules. The monolith consists of a whole block of highly connected pipes, and the fluid flows in the evenly distributed pipes. The monolith matrix is composed of polymers, and the average diameter of its internal pipes is 2μm. Inside the monolith, each pipe is connected to dozens of other pipes. The high connectivity of the pipes helps to evenly distribute the fluid, reduce the operating pressure, and achieve high flow rate and low column pressure.
[0004] At present, the materials of the monolithic column are polymethacrylate polymers or polystyrene polymers. They currently have many commercially successful products on the market, which are relatively successful monolithic column solutions. However, polymethacrylate polymers and polystyrene polymers also have the following problems: 1) The molding temperature is high. When preparing larger size blocks, the process control is complicated due to the thermal effect, the distribution uniformity of the cut channels is poor, and the pore size double distribution phenomenon may occur. In addition, the curing molding is generally at 60-80°C, the time is 12-24 hours, and the cycle is long; 2) After curing molding, the hydrophobicity is strong. In the process of biomacromolecule purification, the non-specific adsorption phenomenon is more obvious. Generally, hydrophilic modification (such as using hydroxyl-rich molecules) is required to reduce the problem of non-specific adsorption; 3) When solidified into a larger pore size, due to its poor toughness, it is easy to be damaged, affecting the use effect. These are the technical problems that monolithic columns will encounter when facing the enrichment and separation of biomacromolecules, and they are also the technical problems that the present invention wants to solve.
[0005] CN202211600949.6 discloses a chromatography material based on epoxy resin, which has uniform internal structure, good preparation reproducibility, high toughness, modifiable functional ligands and high hydrophilicity. CN113145088A discloses a hydrophilic monolithic material and its preparation and application, wherein the monomer triglycidylisocyanurate (TGIC) and 1,4,7,10-tetraazacyclododecane (1,4,7,10-Tetraazacyclododecane, cyclen) are ultrasonically dissolved in an organic solvent, and then an epoxy-amine ring-opening polymerization reaction is carried out under heating conditions to form a monolithic material. Since epoxy reacts with amines to generate a large amount of hydroxyl groups, the monolithic material obtained has good hydrophilicity. EP2485836A1 discloses a monolithic column with fixed monomeric avidin for enriching and identifying biotinylated species, which comprises a stationary phase made of a monolithic material containing a reactive group, and avidin is bound to it, monomerized and renatured.
[0006] At present, when facing the separation of biological macromolecules, especially when facing the enrichment and separation of nucleic acid substances from mixed materials including proteins and nucleic acids, the monolithic column needs to further improve the specific adsorption of biological macromolecules on the basis of general excellent adsorption performance, uniform results, low operating pressure and high flow rate. Summary of the invention
[0007] The technical problem to be solved by the present invention is to overcome the existing technology that the monolithic column is not optimized for biomacromolecules, especially nucleic acid substances, so the yield is low (generally 60%-80%), the stability is poor, the linear amplification reproducibility is inconsistent, and the optimization and control of the purification process are complex. In addition, the temperature control of the curing molding process is complex, the curing cycle is long, etc., resulting in high costs. An epoxy resin-based monolithic column material with specific adsorption capacity for nucleic acids is proposed, which retains the characteristics of excellent adsorption performance, uniform results, low operating pressure, and high flow rate of the epoxy resin monolithic column material, and also has excellent specific enrichment ability for nucleic acid substances.
[0008] To achieve the above object, the present invention proposes the following technical solution.
[0009] The first aspect of the present invention provides an integral column.
[0010] A monolithic column has quaternary ammonium salt groups grafted onto the inner surfaces of the pores and channels.
[0011] In some embodiments, the quaternary ammonium salt group is EP-OCH2CH(OH)CH-N + R 1 R 2 R 3exists in the form of.
[0012] in:
[0013] EP is epoxy resin;
[0014] R 1 , R 2 , R 3 is an alkyl, alkenyl, alkynyl, cycloalkyl, heterocycloalkyl, poly(alkylene oxide) group, poly(alkylene amine) group, polyvinyl alcohol group, or polyvinyl amine group; wherein the alkyl, alkenyl, alkynyl, cycloalkyl, heterocycloalkyl, poly(alkylene oxide) group, poly(alkylene amine) group, polyvinyl alcohol group, or polyvinyl amine group is optionally substituted by an amino, hydroxyl, -C 1-6 Alkyl, -C 1-6 Hydroxyalkyl, -C 1-6 The aminoalkyl group is substituted or hybridized with O, N, Si, P, or S.
[0015] The alkyl group is preferably a methyl, ethyl, 1-propyl, 2-propyl, 1-butyl, 2-methyl-1-propyl, 1-methylpropyl, 1,1-dimethylethyl, 1-pentyl, 2-pentyl, 3-pentyl, 2-methyl-2-butyl, 3-methyl-2-butyl, 3-methyl-1-butyl, 2-methyl-1-butyl, 1-hexyl, 2-hexyl, 3-hexyl, 2-methyl-2-pentyl, 3-methyl-2-pentyl, 4-methyl-2-pentyl, 3-methyl-3-pentyl, 2-methyl-3-pentyl, 2,3-dimethyl-2-butyl and 3,3-dimethyl-2-butyl group.
[0016] The alkenyl group is preferably vinyl, prop-1-enyl, prop-2-enyl, 2-methylprop-1-enyl, but-1-enyl, but-2-enyl, but-3-enyl, butane-1,3-dienyl, 2-methylbut-1,3-dienyl, hex-1-enyl, hex-2-enyl, hex-3-enyl, hex-4-enyl, and hexa-1,3-dienyl groups.
[0017] The alkynyl groups are preferably ethynyl, 1-propynyl, 2-propynyl (propargyl), 1-butynyl, 2-butynyl, and 3-butynyl groups.
[0018] The cycloalkyl group is preferably a cyclopropyl, cyclobutyl, cyclopentyl, 1-cyclopent-1-enyl, 1-cyclopent-2-enyl, 1-cyclopent-3-enyl, cyclohexyl, 1-cyclohex-1-enyl, 1-cyclohex-2-enyl, 1-cyclohex-3-enyl, cyclohexadienyl, cycloheptyl, cyclooctyl group.
[0019] The heterocycloalkyl group is preferably a pyrrolidinyl, imidazolidinone, pyrazolidinyl, piperidinyl, 2,5-piperazinyl, pyranyl, morpholinyl group.
[0020] The poly(alkylene oxide) group is preferably a polyethylene glycol group, a polypropylene glycol group, or a polybutylene glycol group, and the terminal group is preferably a hydroxyl group or an amino group. The molecular weight is preferably 500-5000, preferably 1000-5000, preferably 2000-4000, preferably 2500-3500, and preferably 3000.
[0021] The poly(alkyleneamine) group is preferably polyethylenediamine, polypropylenediamine, or polybutylenediamine, and the terminal group is preferably hydroxyl, amino, or C 1-6 The substituted amine group preferably has a molecular weight of 500-5000, preferably 1000-5000, preferably 2000-4000, preferably 2500-3500, preferably 3000.
[0022] The polyvinyl alcohol group is preferably an end or middle portion of polyvinyl alcohol and EP-OCH2CH(OH)CH-N + The preferred molecular weight is 500-5000, preferably 1000-5000, preferably 2000-4000, preferably 2500-3500, preferably 3000.
[0023] The polyvinylamine group is preferably an end or middle portion of polyvinyl alcohol and EP-OCH2CH(OH)CH-N + The preferred molecular weight is 500-5000, preferably 1000-5000, preferably 2000-4000, preferably 2500-3500, preferably 3000.
[0024] In some embodiments, the EP-OCH2CH(OH)CH-NR 1 R 2 R 3 The anion exchange capacity of the epoxy resin in the form of is 20 μmol / mL-200 μmol / mL, preferably 20 μmol / mL, 30 μmol / mL, 40 μmol / mL, 50 μmol / mL, 60 μmol / mL, 70 μmol / mL, 80 μmol / mL, 90 μmol / mL, 100 μmol / mL, 110 μmol / mL, 120 μmol / mL, 130 μmol / mL, 140 μmol / mL, 150 μmol / mL, 160 μmol / mL, 170 μmol / mL, 180 μmol / mL, 190 μmol / mL, 200 μmol / mL.
[0025] In some embodiments, the pore size of the monolithic column is 2 μm-6 μm, preferably 2.0 μm, 2.1 μm, 2.2 μm, 2.3 μm, 2.4 μm, 2.5 μm, 2.6 μm, 2.7 μm, 2.8 μm, 2.9 μm, 3.0 μm, 3.1 μm, 3.2 μm, 3.3 μm, 3.4 μm, 3.5 μm, 3.6 μm, 3.7 μm, 3.8 μm, 3.9 μm, 4.0 μm, 4.1 μm, 4.2 μm, 4.3 μm, 4.4 μm, 4.5 μm, 4.6 μm, 4.7 μm, 4.8 μm, 4.9 μm, 5.0 μm, 5.1 μm, 5.2 μm, 5.3 μm, 5.4 μm, 5.5 μm, 5.6 μm, 5.7 μm, 5.8 μm, 5.9 μm, 6. .8μm, 3.9μm, 4.0μm, 4.1μm, 4.2μm, 4.3μm, 4.4μm, 4.5μm, 4.6μm, 4.7μm, 4.8μm, 4.9 μm, 5.0μm, 5.1μm, 5.2μm, 5.3μm, 5.4μm, 5.5μm, 5.6μm, 5.7μm, 5.8μm, 5.9μm, 6.0μm.
[0026] In some embodiments, the pore volume of the integral column is 1.1 mL / g-1.8 mL / g, preferably 1.10 mL / g, 1.15 mL / g, 1.20 mL / g, 1.25 mL / g, 1.30 mL / g, 1.35 mL / g, 1.40 mL / g, 1.45 mL / g, 1.50 mL / g, 1.55 mL / g, 1.60 mL / g, 1.65 mL / g, 1.70 mL / g, 1.75 mL / g, 1.80 mL / g.
[0027] In some embodiments, the porosity of the integral column is 55%-68%, preferably 55.0%, 55.5%, 56.0%, 56.5%, 57.0%, 57.5%, 58.0%, 58.5%, 59.0%, 59.5%, 60.0%, 60.5%, 61.0%, 61.5%, 62.0%, 62.5%, 63.0%, 63.5%, 64.0%, 64.5%, 65.0%, 65.5%, 66.0%, 66.5%, 67.0%, 67.5%, 68.0%.
[0028] In some embodiments, the raw material of the monolithic column includes a substance A containing multiple epoxy groups.
[0029] The substance containing multiple epoxy groups refers to a substance containing two or more epoxy groups in its structure.
[0030] In some embodiments, the substance containing multiple epoxy groups is preferably a polyepoxy glycidyl ether substance, or a polyepoxy glycidyl ester substance.
[0031] In some embodiments, the glycidyl ether substance may be one or more monomers satisfying the following structural formula I:
[0032]
[0033] In structural formula Ⅰ, R 1 is selected from hydrogen atom, substituted or unsubstituted C 1 -C 10 An alkyl group, or an epoxy group;
[0034] n is a positive integer from 0 to 10;
[0035] L 1 is selected from an oxygen atom or a nitrogen atom;
[0036] L 2 is selected from an oxygen atom or a nitrogen atom;
[0037] X is selected from substituted or unsubstituted C 1 -C 10 Alkylene, substituted or unsubstituted C 3 -C 10 The cycloalkylene group,
[0038]
[0039] Or, a benzene ring.
[0040] Preferably, the glycidyl ether substance is one or more of the following monomers (a)-(m);
[0041]
[0042] The above structure (a) is the structure of glycerol triglycidyl ether.
[0043] The above structure (b) is the structure of pentaerythritol tetraglycidyl ether.
[0044] The above structure (j) is the structure of 1,4-butanediol diglycidyl ether.
[0045] The above structure (k) is the structure of trimethylolethane triglycidyl ether.
[0046] The above structure (1) is the structure of bisphenol A diglycidyl ether.
[0047] The above structure (m) is the structure of bisphenol F diglycidyl ether.
[0048] In some embodiments, the glycidyl ether material may be one or more polymers satisfying the following structural formula II:
[0049]
[0050] In structural formula II, R 2 is selected from hydrogen atom, substituted or unsubstituted C 1 -C10 Alkyl, or
[0051] m is a positive integer from 2 to 40.
[0052] Preferably, the glycidyl ether substance is one or more of the following polymers (1)-(4);
[0053]
[0054] In some embodiments, the glycidyl ester substance may be one or more monomers satisfying the following structural formula III;
[0055]
[0056] In formula III, Y is selected from substituted or unsubstituted C 1 -C 10 Alkylene, substituted or unsubstituted C 3 -C 10 A cycloalkylene ring, or a benzene ring.
[0057] Preferably, the glycidyl ester substance is the following monomer (A) and / or (B);
[0058]
[0059] In some embodiments, the substance containing multiple epoxy groups is preferably one or more of the following monomers (I)-(IV);
[0060]
[0061] In some embodiments, the substance containing multiple epoxy groups is preferably a polyepoxy glycidyl ether monomer and / or a polyepoxy glycidyl ether polymer.
[0062] Wherein, the polyepoxy group glycidyl ether monomer may be glycerol triglycidyl ether and / or pentaerythritol tetraglycidyl ether.
[0063] Wherein, the polyepoxy glycidyl ether polymer may be polyglycerol glycidyl ether and / or polypentaerythritol tetraglycidyl ether.
[0064] In some embodiments, when the substance containing polyepoxy groups is a mixture of the polyepoxy glycidyl ether monomer and the polyepoxy glycidyl ether polymer, the mixed volume ratio of the polyepoxy glycidyl ether monomer and the polyepoxy glycidyl ether polymer may be (0.1-9):1, such as 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1 or 8:1. For example, a mixture of polyglycerol triglycidyl ether: pentaerythritol tetraglycidyl ether = 1:1, or polypentaerythritol tetraglycidyl ether: glycerol triglycidyl ether = 1:1.
[0065] In some embodiments, the molecular weight of the substance containing multiple epoxy groups may be 300-2000, such as a molecular weight of 550, a molecular weight of 700, a molecular weight of 1000, a molecular weight of 1200, a molecular weight of 1500, or a molecular weight of 1800.
[0066] In some embodiments, the raw material A may further include a substance containing a monoepoxy group. The substance containing a monoepoxy group refers to a substance containing one epoxy group in its structure.
[0067] The substance containing a monoepoxy group is preferably a monoepoxy glycidyl ether substance, or a monoepoxy glycidyl ester substance.
[0068] The monoepoxy glycidyl ether substance may be a substance having a conventional structure containing one epoxy group in the art, preferably phenyl glycidyl ether and / or butyl glycidyl ether.
[0069] The monoepoxy glycidyl ester substance may be one or more of phenyl glycidyl ether, butyl glycidyl ether, amyl glycidyl ether, octyl glycidyl ether, octadecyl glycidyl ether and naphthyl glycidyl ether, preferably phenyl glycidyl ether and / or butyl glycidyl ether.
[0070] In some embodiments, the raw material of the monolithic column includes porogen B.
[0071] In some embodiments, the porogen B is a solvent that is miscible with the substance A containing multiple epoxy groups and does not undergo polycondensation, preferably one or more of toluene, xylene, dichloromethane, dichloroethane, dioxane, formamide (DMF), dimethyl sulfoxide (DMSO) and methyl tert-butyl ether, more preferably one or more of toluene, dioxane and methyl tert-butyl ether, such as toluene and dioxane, toluene and methyl tert-butyl ether, or dioxane and methyl tert-butyl ether.
[0072] In some embodiments, when the porogen B is a mixture of two different substances, the volume ratio of the two different substances may be (0.1-9):1, such as 0.5:1, 1:1, 2:1, 3:1, 5:1 or 7:1.
[0073] In some embodiments, the weight of the raw material A is preferably 22%-70%, such as 25%, 30%, 35%, 40%, 45%, 50%, 55%, 58%, 65% or 68% of the total weight of the raw material A and the porogen B. The weight of the porogen B is preferably 35%-80%, such as 40%, 45%, 50%, 60%, 65%, 70%, 75% or 78% of the total weight of the raw material A and the porogen B.
[0074] In some embodiments, the raw material A is a polyepoxy glycidyl ether monomer and / or a polyepoxy glycidyl ether polymer; the porogen B is one or more of toluene, xylene, dichloromethane, dichloroethane, dioxane, formamide (DMF), dimethyl sulfoxide (DMSO) and methyl tert-butyl ether.
[0075] In some embodiments, the raw material A is a polyepoxy glycidyl ether polymer and a monoepoxy glycidyl ether monomer; the porogen B is one or more of toluene, xylene, dichloromethane, dichloroethane, dioxane, formamide (DMF), dimethyl sulfoxide (DMSO) and methyl tert-butyl ether.
[0076] In some embodiments, the raw material A is polypropylene triglycidyl ether and a monoepoxy glycidyl ether monomer; the porogen B is one or more of toluene, xylene, dichloromethane, dichloroethane, dioxane, formamide (DMF), dimethyl sulfoxide (DMSO) and methyl tert-butyl ether; the monoepoxy glycidyl ether monomer is preferably phenyl glycidyl ether and / or butyl glycidyl ether.
[0077] In some embodiments, the raw material A is polypropylene triglycidyl ether and monoepoxy glycidyl ether monomers; the porogen B is one or more of toluene, dioxane and methyl tert-butyl glyceryl ether; the monoepoxy glycidyl ether monomer is preferably phenyl glycidyl ether and / or butyl glycidyl ether.
[0078] In some embodiments, the raw material of the monolithic column includes catalyst C.
[0079] In some embodiments, the catalyst C may be a Lewis acid and / or a Lewis acid complex.
[0080] The Lewis acid may be one or more of aluminum trichloride, boron trifluoride, ferric bromide, ferric chloride, zinc chloride, niobium trichloride pentachloride and sulfur trioxide, such as boron trifluoride.
[0081] The Lewis acid complex may be one or more of boron trifluoride ethyl ether, boron trifluoride acetonitrile, boron trifluoride dimethyl carbonate and boron trifluoride ethylamine.
[0082] In some embodiments, the weight of the catalyst C is preferably 0.3‰-1‰, such as 0.4‰, 0.5‰, 0.6‰, 0.7‰, 0.8‰ or 0.9‰, based on the total weight of the raw material A and the porogen B.
[0083] In some embodiments, the raw material of the monolithic column includes a quaternary ammonium salt modifier D.
[0084] In some embodiments, the quaternary ammonium salt modifier D has NR 1 R 2 R 3 exists in the form of.
[0085] Among them, R 1 , R 2 , R 3 is an alkyl, alkenyl, alkynyl, cycloalkyl, heterocycloalkyl, poly(alkylene oxide) group, poly(alkylene amine) group, polyvinyl alcohol group, or polyvinyl amine group; wherein the alkyl, alkenyl, alkynyl, cycloalkyl, heterocycloalkyl, poly(alkylene oxide) group, poly(alkylene amine) group, polyvinyl alcohol group, or polyvinyl amine group is optionally substituted by an amino, hydroxyl, -C 1-6 Alkyl, -C 1-6 Hydroxyalkyl, -C 1-6 The aminoalkyl group is substituted or hybridized with O, N, Si, P, or S.
[0086] The alkyl group is preferably a methyl, ethyl, 1-propyl, 2-propyl, 1-butyl, 2-methyl-1-propyl, 1-methylpropyl, 1,1-dimethylethyl, 1-pentyl, 2-pentyl, 3-pentyl, 2-methyl-2-butyl, 3-methyl-2-butyl, 3-methyl-1-butyl, 2-methyl-1-butyl, 1-hexyl, 2-hexyl, 3-hexyl, 2-methyl-2-pentyl, 3-methyl-2-pentyl, 4-methyl-2-pentyl, 3-methyl-3-pentyl, 2-methyl-3-pentyl, 2,3-dimethyl-2-butyl and 3,3-dimethyl-2-butyl group.
[0087] The alkenyl group is preferably vinyl, prop-1-enyl, prop-2-enyl, 2-methylprop-1-enyl, but-1-enyl, but-2-enyl, but-3-enyl, butane-1,3-dienyl, 2-methylbut-1,3-dienyl, hex-1-enyl, hex-2-enyl, hex-3-enyl, hex-4-enyl, and hexa-1,3-dienyl groups.
[0088] The alkynyl groups are preferably ethynyl, 1-propynyl, 2-propynyl (propargyl), 1-butynyl, 2-butynyl, and 3-butynyl groups.
[0089] The cycloalkyl group is preferably a cyclopropyl, cyclobutyl, cyclopentyl, 1-cyclopent-1-enyl, 1-cyclopent-2-enyl, 1-cyclopent-3-enyl, cyclohexyl, 1-cyclohex-1-enyl, 1-cyclohex-2-enyl, 1-cyclohex-3-enyl, cyclohexadienyl, cycloheptyl, cyclooctyl group.
[0090] The heterocycloalkyl group is preferably a pyrrolidinyl, imidazolidinone, pyrazolidinyl, piperidinyl, 2,5-piperazinyl, pyranyl, morpholinyl group.
[0091] The poly(alkylene oxide) group is preferably a polyethylene glycol group, a polypropylene glycol group, or a polybutylene glycol group, and the terminal group is preferably a hydroxyl group or an amino group. The molecular weight is preferably 500-5000, preferably 1000-5000, preferably 2000-4000, preferably 2500-3500, and preferably 3000.
[0092] The poly(alkyleneamine) group is preferably polyethylenediamine, polypropylenediamine, or polybutylenediamine, and the terminal group is preferably hydroxyl, amino, or C 1-6 The substituted amine group preferably has a molecular weight of 500-5000, preferably 1000-5000, preferably 2000-4000, preferably 2500-3500, preferably 3000.
[0093] The polyvinyl alcohol group is preferably an end portion or a middle portion of polyvinyl alcohol and N + The preferred molecular weight is 500-5000, preferably 1000-5000, preferably 2000-4000, preferably 2500-3500, preferably 3000.
[0094] The polyvinylamine group is preferably an end portion or a middle portion of polyvinyl alcohol and N + The preferred molecular weight is 500-5000, preferably 1000-5000, preferably 2000-4000, preferably 2500-3500, preferably 3000.
[0095] The second aspect of the present invention provides a method for preparing a monolithic column.
[0096] The preparation method comprises the following steps:
[0097] S1. Hydroxylating the monolithic column;
[0098] S2. Quaternizing the hydroxylated monolithic column.
[0099] Wherein in step S1, hydroxylation comprises the following steps:
[0100] S11. Cleaning the monolithic column;
[0101] S12. Drying the monolithic column;
[0102] S13. Hydroxylated monolithic column;
[0103] S14. Post-processing.
[0104] In the step S11, a piece of the monolithic column is taken and eluted with deionized water with a volume of 10-20 times to remove the protective solution.
[0105] In step S12, the monolithic column is drained with a vacuum pump. The draining time is 10-120 min, preferably 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min. The draining temperature is 5-50°C, preferably 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C.
[0106] In the step S13, an acidic aqueous solution is added into the dried monolithic column, and the temperature is raised to react, so that the residual epoxy groups in the monolithic column are converted into hydroxyl groups.
[0107] The acid in the acidic aqueous solution is sulfuric acid, hydrochloric acid, nitric acid, formic acid, or acetic acid. The concentration of the acid in the acidic aqueous solution is 0.1-0.5M, preferably 0.2M, 0.3M, or 0.4M.
[0108] The volume ratio of the acidic aqueous solution to the monolithic column is (3-30):1, preferably 5:1, 7:1, 10:1, 15:1, 20:1, 25:1, 30:1.
[0109] The temperature-raising reaction is to raise the temperature of the system to 40-80°C and react for 1-6 hours. The temperature is preferably 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C. The reaction time is preferably 1.0h, 1.5h, 2.0h, 2.5h, 3.0h, 3.5h, 4.0h, 4.5h, 5.0h, 5.5h, 6.0h.
[0110] In the step S14, the hydroxylated monolithic column is rinsed with deionized water until the pH is neutral.
[0111] In some embodiments, after step S1, the epoxy group density of the whole column after hydroxylation is determined to be 0 or undetectable by epoxy group density measurement.
[0112] Wherein in step S2, quaternization comprises the following steps:
[0113] S21. Cleaning the monolithic column;
[0114] S22. Drying the monolithic column;
[0115] S23. Quaternary ammonium salt monolithic column;
[0116] S24. Neutralization and post-treatment.
[0117] In the step S21, a piece of the monolithic column is taken and eluted with deionized water with a volume of 10-20 times to remove the protective solution.
[0118] In step S22, the monolithic column is drained with a vacuum pump. The draining time is 10-120 min, preferably 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min. The draining temperature is 5-50°C, preferably 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C.
[0119] In step S23, a quaternary ammonium salt modifier D solution is added into the monolithic column, and after being fully soaked, a catalyst is added and the temperature is raised to react so that the hydroxyl groups in the monolithic column are converted into quaternary ammonium salt groups.
[0120] In step S23, the quaternary ammonium salt modifier D solution may be mixed with the catalyst, and then the monolithic column may be added and heated to react so that the hydroxyl groups in the monolithic column are converted into quaternary ammonium salt groups.
[0121] The quaternary ammonium salt modifier D solution is an aqueous solution of quaternary ammonium salt modifier D, and the concentration is 40%-70% (mass volume ratio g / mL), preferably 40%, 45%, 50%, 55%, 60%, 65%, 70%.
[0122] The catalyst is alkaline or acidic cerium ammonium nitrate.
[0123] The alkali is one or more of potassium hydroxide and sodium hydroxide, and the concentration is 3%-10%, preferably 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%.
[0124] The acidic ammonium cerium nitrate is a mixture of ammonium cerium nitrate and an acid, and the acid is one or more of sulfuric acid, hydrochloric acid, nitric acid, formic acid, and acetic acid.
[0125] The amount of the ammonium cerium nitrate added is 1-10% (mass volume ratio g / mL (solvent volume)), preferably 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%. The amount of the acid added is 0.1%-1% (mass volume ratio g / mL (solvent volume)), preferably 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%.
[0126] The addition amount of the quaternary ammonium salt modifier D solution is 5mL-20mL / block mL, preferably 5mL, 6mL, 7mL, 8mL, 9mL, 10mL, 11mL, 12mL, 13mL, 14mL, 15mL, 16mL, 17mL, 18mL, 19mL, 20mL.
[0127] The temperature-raising reaction is to raise the temperature of the system to 40-80°C and react for 10-48h. The temperature is preferably 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C. The reaction time is preferably 10h, 12h, 15h, 18h, 21h, 24h, 27h, 30h, 33h, 36h, 39h, 42h, 45h, 48h.
[0128] In the step S24, the quaternized monolithic column is washed with a pH adjuster and then washed with deionized water until the pH is neutral.
[0129] The pH regulator is an acid or a base. The acid is one or more of sulfuric acid, hydrochloric acid, nitric acid, formic acid, and acetic acid. The base is one or more of sodium hydroxide, potassium hydroxide, and ammonia water.
[0130] After step S24 is completed, the monolithic column may be stored in a 20%-70% ethanol solution for future use in order to protect it.
[0131] The third aspect of the present invention provides an application of a monolithic column for enrichment and separation of DNA or RNA.
[0132] The monolithic column has the function of specifically adsorbing DNA or RNA. Specifically, it can specifically adsorb DNA and / or RNA in a mixed solution containing biomacromolecules, so that the DNA and / or RNA can be enriched in the monolithic column and then eluted and separated.
[0133] A fourth aspect of the present invention is to provide a chromatographic column comprising the aforementioned monolithic column.
[0134] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0135] The reagents and raw materials used in the present invention are commercially available.
[0136] The positive and progressive effects of the present invention are:
[0137] 1. The monolithic column prepared by the present invention is rich in hydroxyl groups and has excellent compatibility with elution objects containing biological macromolecules, and is particularly suitable for the field of biological macromolecule chromatography.
[0138] 2. The monolithic column prepared by the present invention retains the characteristics of excellent adsorption performance, uniform results, low operating pressure and high flow rate of epoxy resin monolithic column materials. The pores are adjustable, submicron-micron level, relatively uniformly distributed, and present a single-peak normal distribution, with high ligand utilization. The pores are through holes, without diffusion effect, no need to increase retention time, shorten process cycle, no obvious eddy current phenomenon, low shear force, no effect on sample load at high flow rate, and high toughness.
[0139] 3. The monolithic column prepared by the present invention has excellent specific adsorption capacity for nucleic acid substances and is suitable for the enrichment and separation of DNA and / or RNA substances. BRIEF DESCRIPTION OF THE DRAWINGS
[0140] Figure 1 This is the pore size distribution diagram of the integral column block prepared in Preparation Example 3.
[0141] Figure 2 This is the pore size distribution diagram of the integral column block prepared in Example 7.
[0142] Figure 3 This is a scanning electron microscope image of the integral column block prepared in Example 1.
[0143] Figure 4 This is a scanning electron microscope image of the integral column block prepared in Comparative Example 12.
[0144] Figure 5 This is a chromatography experiment diagram of the integral housing block prepared in Example 1.
[0145] Figure 6 This is a chromatography experiment diagram of the integral housing block prepared in Example 7.
[0146] Figure 7 This is a chromatography experiment diagram of the integral housing block prepared in Example 13. DETAILED DESCRIPTION
[0147] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0148] Unless otherwise specified, the reagents used in the following examples and comparative examples are all conventional commercially available products in the art.
[0149] Preparation Example
[0150] S1 Hydroxylation: Take 1 mL of the monolithic column and wash it with deionized water for 20 times the volume on a sand core funnel to remove the protective liquid. Use a vacuum pump to drain the sand core funnel for 60 minutes at an ambient temperature of 25°C.
[0151] The 1 mL monolithic column block after being drained was transferred to a glass reaction bottle, and a 0.2 M deionized sulfuric acid solution was added, with the amount added being 10 mL of reaction solution / block (1 mL); ultrasonication was performed for 30 min to accelerate the rapid immersion of the reaction solution into the monolithic column block; after the ultrasonication, the glass reaction bottle was transferred to a water bath, heated to 60°C, and kept warm for 4 h; the hydroxylated monolithic column block was placed on a sand core funnel and rinsed with deionized water until the pH was neutral (6.5-7).
[0152] Through the epoxy group density measurement, it was determined that the block epoxy group density after hydroxylation was 0;
[0153] Table 1 Performance of hydroxylated monolithic column preparation example
[0154]
[0155] N / A: No hydroxylation
[0156] The epoxy group density measurement shows that the remaining epoxy groups in Preparation Examples 1-4 are all converted into hydroxyl groups, which can be used for the next coupling treatment. Comparative Preparation Examples 1-4 show that the residual epoxy group density is negatively correlated with the pore size.
[0157] Example
[0158] Method 1:
[0159] 1. Prepare 40-70% aqueous solution of solvent A (mass volume ratio g / mL) in a glass reaction bottle (10mL / ml).
[0160] 2. Add the hydroxylated chromatographic stack to the above reaction system, shake quickly, and ultrasonic / vacuum for 15 minutes.
[0161] 3. Weigh 5% NaOH (mass volume ratio g / mL (solvent volume)) of the reaction solvent and add it to the above system. After adding, shake it quickly and sonicate for 15 minutes.
[0162] 4. After the ultrasound is completed, place it in a water bath shaker at 50-70℃, 100rpm, for 24h.
[0163] 5. First wash with 1M hydrochloric acid, then wash with deionized water until the pH value is neutral (6.5-7), and store with 20% ethanol for later use.
[0164] Method 2:
[0165] 1. Prepare 40-70% aqueous solution of solvent A (mass volume ratio g / mL) and 5% aqueous solution of NaOH (mass volume ratio g / mL (solvent volume)) of the reaction solvent in a glass reaction bottle (10 mL / ml).
[0166] 2. Add the hydroxylated chromatographic stack to the above reaction system, shake quickly, and ultrasonic / vacuum for 15 minutes.
[0167] 3. After the ultrasound is completed, place it in a water bath shaker at 50-70℃, 100rpm, for 24h.
[0168] 4. First wash with 1M hydrochloric acid, then wash with deionized water until the pH value is neutral (6.5-7), and store with 20% ethanol for later use.
[0169] Method 3:
[0170] 1. Prepare 5% cerium nitrate ammonium and 0.5% sulfuric acid (mass volume ratio g / mL (solvent volume)) aqueous solution and mix thoroughly in a glass reaction bottle (10mL / ml);
[0171] 2. Add the hydroxylated chromatographic stack to the above reaction system, shake well quickly, and ultrasonic / vacuum for 15 minutes;
[0172] 3. Pre-react the above system for 30 minutes at 30°C; add 20-50% of solvent A to the above system, mix well, and ultrasonic / vacuum for 15 minutes;
[0173] 4. Place in a water bath and react at 30-50℃ for 6h;
[0174] 5. First wash with 1M sodium hydroxide, then wash with deionized water until the pH value is neutral (6.5-7), and store with 20% ethanol for later use.
[0175] Method 4:
[0176] 1. Prepare 5% cerium nitrate ammonium, 0.5% sulfuric acid and 20-50% A solvent (mass volume ratio g / mL (solvent volume)) aqueous solution, and mix thoroughly in a glass reaction bottle (10mL / ml);
[0177] 2. Add the hydroxylated chromatographic stack to the above reaction system, shake well quickly, and ultrasonic / vacuum for 15 minutes;
[0178] 3. Place in a water bath and react at 30-50℃ for 6h;
[0179] 4. First wash with 1M sodium hydroxide, then wash with deionized water until the pH value is neutral (6.5-7), and store with 20% ethanol for later use.
[0180] Table 2 Examples and Comparative Examples
[0181]
[0182]
[0183]
[0184] Effect test
[0185] Pore size distribution, pore volume, and porosity determination
[0186] Test method: Mercury intrusion method
[0187] Test equipment: USA-McMerrittick-autoporeV 9620
[0188] Test results:
[0189] After hydroxylation chromatography stack coupling modification, the pore size, porosity and pore volume are basically stable, indicating that the pore structure is not destroyed during the reaction modification process.
[0190] Figure 1 To prepare the pore size distribution diagram of the hydroxylated block obtained in Example 3, Figure 2 The pore size distribution diagram after quaternary ammonium salt finishing column prepared in Example 7 is shown in Table 2, and the pore size distribution results are consistent.
[0191] The test results of various embodiments and comparative examples are shown in Table 3.
[0192] Table 3 Pore size distribution, pore volume, porosity test results
[0193]
[0194]
[0195] Field emission electron microscope scanning test
[0196] Test objects: Example 1, Comparative Example 12
[0197] Test equipment: Germany-Zeiss sigma300, Oxford spectroscopy.
[0198] Test results:
[0199] The electron microscopy results show that the pore structure is consistent after coupling modification, and the pore structure is still not affected under the conditions of higher concentration and higher temperature in comparative example 5. This is consistent with the results of mercury intrusion testing, indicating that this method of modifying the monolithic column can achieve functionalization while maintaining its basic properties such as pore size.
[0200] Epoxy ligand density determination
[0201] Test objects: Preparation examples 1-4 and comparative examples 1-4 in Table 1
[0202] Test method: Sodium thiosulfate-hydrochloric acid titration method.
[0203] The chromatographic materials of Preparation Examples 1-4 and Comparative Examples 1-4 modified with epoxy were cleaned with deionized water, placed in a sand core funnel and vacuum-dried for 10 minutes, and then weighed 1 piece (about 0.5g) and placed in a ground-mouth conical flask, 3mL, 1.3mol / L sodium thiosulfate and 1-2 drops of phenolphthalein indicator were added, and the conical flask was sealed and placed at room temperature for 1 hour. The supernatant solution after the reaction was titrated with 0.1mol / L hydrochloric acid standard solution until the red solution became colorless. Substitute the consumed volume of hydrochloric acid standard solution into the following formula to calculate the epoxy ligand density:
[0204] S=1000*[M HCl (V 0 -V 1 )*ρ / W]
[0205] S: epoxy ligand density, μmol / mL;
[0206] M HCl : hydrochloric acid concentration, mmol / mL;
[0207] V 0 , V 1 : Volume of HCl before and after titration, mL;
[0208] ρ: medium density (1.2 g / mL);
[0209] W: The mass of the whole block weighed (g).
[0210] Test equipment: acid-base titration device.
[0211] Test results: See Table 1.
[0212] From the data in Table 1, it can be seen that the hydroxylation-treated chromatographic column block has almost no epoxy groups, while the unhydroxylation-treated block still has residual epoxy groups, which are negatively correlated with the pore size. The larger the pore, the smaller the epoxy group density. This indicates that the hydroxylation treatment is a necessary step for the subsequent coupling of quaternary ammonium salt compounds.
[0213] Anion exchange capacity determination
[0214] Test object: quaternary ammonium salt anion exchange monolithic columns prepared in Examples 1-18 and Comparative Examples 1-11 in Table 2 above.
[0215] Determination method: GB 5760-86.
[0216] Test equipment: acid-base titration device.
[0217] Test results: as shown in Table 4 below.
[0218] Table 4 Anion exchange capacity results of each embodiment and comparative example
[0219]
[0220]
[0221] In Examples 1-18, as the anion exchange capacity of the quaternary ammonium salt increases with the pore size, it gradually decreases. And the ion exchange capacity is basically in the range of 70-180 μmol / mL, which is suitable for the density requirements of the chromatography ligand; the coupling efficiency of olefin quaternary ammonium salt compounds is relatively ideal, and its anion exchange capacity is basically above 120 μmol / mL in a monolithic column with a smaller pore size (average pore size 2.7 μum). Except for Example 6, it may be that the atomic radius of the bromide ion is larger than that of the chloride ion, the electrons are more active, the ion action is stronger, and the exchange difficulty is greater. After the coupling of the remaining olefin quaternary ammonium salt compounds, there are carbonyl, amide, methyl, hydroxyl and other groups, which can adjust the ion elution intensity of biomacromolecules through hydrogen bonding, dipole moment, polar non-polar differences. From the aspects of industrial preparation cost and efficiency, 2,3-epoxypropyltrimethylammonium chloride is preferred, followed by allyltrimethylammonium chloride and others.
[0222] The anion exchange capacity results of Example 7 and Comparative Example 11 were 138.2 μmoL / mL and 90.8 μmoL / mL, respectively, indicating that the hydroxylation process significantly increased the anion exchange density;
[0223] The anion exchange capacity results of Example 7 and Comparative Example 1 were 138.2 μmoL / mL and 98.2 μmoL / mL, respectively, indicating that the coupling efficiency of method 1 was high after premixing the 2,3-epoxypropyltrimethylammonium chloride solution with the monolithic column block by ultrasonication for 15 minutes and then adding sodium hydroxide. The one-pot method of method 2 premixed all reagents, which may be that the 2,3-epoxypropyltrimethylammonium chloride was partially destroyed by the strong sodium oxide and did not have time to contact the internal pore surface of the monolithic column;
[0224] The anion exchange capacity results of Comparative Examples 2, 3, 4, and 5 were 112.8 μmoL / mL, 120.8 μmoL / mL, 122.5 μmoL / mL, and 124.8 μmoL / mL, respectively. Compared with Example 7, the anion exchange densities were all relatively low, indicating that the temperature and the content of 2,3-epoxypropyltrimethylammonium chloride solution were too high or too low, which would affect the coupling efficiency. It is speculated that if the solvent concentration is too high, the diffusion effect of the solid-liquid reaction will be affected, and if the concentration is too low, the contact opportunity of the local pore surface will be affected; if the temperature is too high, the reaction rate of 2,3-epoxypropyltrimethylammonium chloride with the integral column block may be slower than the rate of epoxy destruction itself.
[0225] The anion exchange capacity results of Comparative Examples 6-10 were 101.2 μmoL / mL, 98.2 μmoL / mL, 91.2 μmoL / mL, 98.6 μmoL / mL, and 102.0 μmoL / mL, respectively. Compared with Example 8 (121.6 μmoL / mL), Comparative Example 6 adopted the one-pot method of Method 4, indicating that the coupling efficiency was significantly lower than the scheme of pre-reacting first and then adding solvent A in Method 3. The anion exchange density of Comparative Examples 7-10 was relatively low, indicating that too much or too little addition of solvent A or too high a temperature would affect the coupling efficiency.
[0226] Plasmid DNA enrichment test of bacterial lysate
[0227] Test objects: Examples 1-18 and Comparative Examples 1-12
[0228] Test method: as follows
[0229] 1. Preparation of bacterial lysate:
[0230] 1.1. Bacterial strain amplification culture, bacterial strain (Escherichia coli TOP10, pET-30a-rspa, about 6500bp). (Bacterial strain amplification is a routine operation in the field of bioengineering and will not be described in detail here);
[0231] 1.2. Alkaline lysis of the cells: the cells after amplification and culture are centrifuged to collect the cell solids, and the crude plasmid is extracted by the classic three-step alkaline lysis method (this is a routine operation in the field of bioengineering and will not be described in detail here);
[0232] 1.3. Ammonium sulfate / calcium chloride precipitation method to remove RNA, generally the salt concentration is 0.3-2M calcium chloride or ammonium sulfate (this is a routine operation in the field of bioengineering and will not be described in detail here);
[0233] 1.4. Collect the supernatant by centrifugation, which is the crude product before plasmid loading;
[0234] 2. Column chromatography test of lysate:
[0235] 2.1 Place the reacted quaternary ammonium salt anion exchange chromatography stack in a 1 mL radial flow chromatography tool (Yuji Bio-Chromatography Tool);
[0236] 2.2. Connect the chromatography tool containing the quaternary ammonium salt anion exchange block to the liquid chromatography device, use the balance solution W: 50mM Tris-HCl + 10mM EDTA, PH7.2-7.4, balance the column 5-10 times the volume until the conductivity, pH, and UV baseline are stable;
[0237] 2.3. Take the crude plasmid (pET-30a-rspa, 6500bp), dilute with balance to conductivity ≤30ms / cm, inject 150mL through the chromatography equipment injection system, flow rate 5mL / min; use (5%-25% eluent E + 75%-95% balance solution W to wash impurities)
[0238] 2.4 Use eluent E (50mM Tris-HCl+10mM EDTA+2M NaCl, PH7.2-7.4) for gradient elution to collect plasmid DNA at a flow rate of 2-3mL / min; collect eluent samples for micro-ultraviolet spectrophotometry and agarose gel electrophoresis determination
[0239] 2.5. Regeneration: First, use 100% eluent to regenerate the chromatographic column at a flow rate of 2-3 mL / min; then use 1M sodium hydroxide to clean the column, and immediately wash the column with deionized water until it is neutral.
[0240] Chromatography test results: See Table 5 below:
[0241] Table 5 Chromatography test results
[0242]
[0243]
[0244]
[0245]
[0246] As shown in Table 5, the chromatographic stack monolith modified by quaternary ammonium salt has the performance of enriching plasmid DNA from bacterial lysis and removing some impurities by gradient elution. Figure 5 , Figure 6 , Figure 7The chromatograms are respectively those of Examples 1, 7, and 13. FT is the flow-through portion, i.e., the non-negatively charged or very weakly negatively charged molecules in the lysate, W is the washed-away portion of the negatively charged molecules (such as RNA, HCP, other negatively charged small molecules, etc.) bound to the chromatographic stack, E is the eluted DNA of the relatively pure plasmid, and C is the sodium hydroxide regeneration peak. The pore sizes of Examples 1, 7, and 13 increase successively, the specific surface areas decrease successively, and the corresponding ligand densities decrease gradually, so the strong retention decreases successively. The smaller the pore size, the higher the local ligand density, resulting in the inability of some plasmid DNA to be effectively dissociated under a certain ionic strength of the eluent, such as Figure 5-6 shown.
[0247] The chromatographic recoverable loading shown in Table 5 is basically consistent with the anion exchange capacity results in Table 4, and is positively correlated. For example, the loadings of Example 7 and Comparative Example 1 are 3.02 mg (non-saturated loading) and 1.24 mg, respectively. The different coupling modes significantly differ in the amount of plasmid loaded on the chromatographic stack monolithic column with a pore size of 4.2 um; the loadings of Comparative Examples 2-5 are 2.12 mg, 2.77 mg, 2.83 mg, and 2.76 mg, respectively, which are consistent with the above ion exchange capacity results. Similarly, Example 8 and Comparative Examples 6-10 are shown in Table 5.
[0248] The loading capacity of Comparative Example 11 is 1.43 mg, which is significantly decreased compared with Example 7, indicating that the hydroxylation process has a significant effect on increasing the loading capacity.
[0249] The loadings of Example 1 and Comparative Example 12 were 3.01 mg (non-saturated loading, due to the small pore size, part of the plasmid DNA was eluted by sodium hydroxide) and 2.71 mg, respectively. Too high concentration or too high temperature reduced the loading, which is consistent with the anion exchange capacity results. The main reason for the reduction in loading is the coupling efficiency rather than the effect of concentration or temperature on the pores, see Figure 3-4 .
[0250] In Examples 1-6, the elution salt concentration ratio range is 65%-85%; in Examples 7-12, the elution salt concentration ratio range is 55%-78%; in Examples 13-18, the elution salt concentration ratio range is 50%-72%. As the pore size increases, the ligand density gradually decreases, and the elution ion strength gradually decreases, so the elution salt ratio gradually shows a decreasing trend. Compared with conventional weak anion exchange DEAE, strong anion exchange requires a higher salt concentration because the strength of quaternary ammonium salts and hydroxide anions is greater than that of chloride anions, so a higher ratio of ion strength is required for exchange. Examples 5, 11, and 17 are coupled with N, N, N-trimethyl-3-[1-oxo-2-propenylamino]propylammonium chloride ligands. As shown in Table 5, the elution salt concentration ratio is relatively low, probably because it carries an amide group and has a certain hydrogen bond interaction, which can be eluted relatively gently. The elution strength of different ligands can be comprehensively considered based on the binding strength of the purified substance such as plasmid DNA and the difference in impurity binding strength, as well as the selection of pore size, so as to optimize and balance the chromatography process in terms of purity, yield and efficiency to achieve the best effect.
Claims
1. A monolithic column, characterized in that: Quaternary ammonium salt groups are grafted on the inner surfaces of the pores and channels of the monolithic column.
2. The integral column according to claim 1, characterized in that: The quaternary ammonium salt group is EP-OCH2CH(OH)CH-N + R 1 R 2 R 3 exists in the form of; in: EP is epoxy resin; R 1 , R 2 , R 3 is an alkyl, alkenyl, alkynyl, cycloalkyl, heterocycloalkyl, poly(alkylene oxide) group, poly(alkylene amine) group, polyvinyl alcohol group, or polyvinyl amine group; wherein the alkyl, alkenyl, alkynyl, cycloalkyl, heterocycloalkyl, poly(alkylene oxide) group, poly(alkylene amine) group, polyvinyl alcohol group, or polyvinyl amine group is optionally substituted by an amino, hydroxyl, -C 1-6 Alkyl, -C 1-6 Hydroxyalkyl, -C 1-6 The aminoalkyl group is substituted or hybridized with O, N, Si, P, or S.
3. The integral column according to claim 2, characterized in that: The alkyl group is preferably a methyl, ethyl, 1-propyl, 2-propyl, 1-butyl, 2-methyl-1-propyl, 1-methylpropyl, 1,1-dimethylethyl, 1-pentyl, 2-pentyl, 3-pentyl, 2-methyl-2-butyl, 3-methyl-2-butyl, 3-methyl-1-butyl, 2-methyl-1-butyl, 1-hexyl, 2-hexyl, 3-hexyl, 2-methyl-2-pentyl, 3-methyl-2-pentyl, 4-methyl-2-pentyl, 3-methyl-3-pentyl, 2-methyl-3-pentyl, 2,3-dimethyl-2-butyl and 3,3-dimethyl-2-butyl group; The alkenyl group is preferably vinyl, prop-1-enyl, prop-2-enyl, 2-methylprop-1-enyl, but-1-enyl, but-2-enyl, but-3-enyl, butane-1,3-dienyl, 2-methylbut-1,3-dienyl, hex-1-enyl, hex-2-enyl, hex-3-enyl, hex-4-enyl, and hexa-1,3-dienyl groups; The alkynyl group is preferably ethynyl, 1-propynyl, 2-propynyl (propargyl), 1-butynyl, 2-butynyl, and 3-butynyl groups; The cycloalkyl group is preferably a cyclopropyl, cyclobutyl, cyclopentyl, 1-cyclopent-1-enyl, 1-cyclopent-2-enyl, 1-cyclopent-3-enyl, cyclohexyl, 1-cyclohex-1-enyl, 1-cyclohex-2-enyl, 1-cyclohex-3-enyl, cyclohexadienyl, cycloheptyl, cyclooctyl group; The heterocycloalkyl group is preferably a pyrrolidinyl, imidazolidinone, pyrazolidinyl, piperidinyl, 2,5-piperazinyl, pyranyl, morpholinyl group; The poly(alkylene oxide) group is preferably a polyethylene glycol group, a polypropylene glycol group, or a polybutylene glycol group, preferably the terminal group is a hydroxyl group or an amino group, and preferably has a molecular weight of 500-5000, preferably 1000-5000, preferably 2000-4000, preferably 2500-3500, preferably 3000; The poly(alkyleneamine) group is preferably a polyethylenediamine group, a polypropylenediamine group, or a polybutylenediamine group, and the terminal group is preferably a hydroxyl group, an amino group, or a C 1-6 Substituted amine groups, preferably having a molecular weight of 500-5000, preferably 1000-5000, preferably 2000-4000, preferably 2500-3500, preferably 3000; The polyvinyl alcohol group is preferably an end or middle portion of polyvinyl alcohol and EP-OCH2CH(OH)CH-N + Connected, preferably with a molecular weight of 500-5000, preferably 1000-5000, preferably 2000-4000, preferably 2500-3500, preferably 3000; The polyvinylamine group is preferably an end or middle portion of polyvinyl alcohol and EP-OCH2CH(OH)CH-N + The preferred molecular weight is 500-5000, preferably 1000-5000, preferably 2000-4000, preferably 2500-3500, preferably 3000.
4. The integral column according to any one of claims 1 to 3, characterized in that: The EP-OCH2CH(OH)CH -NR 1 R 2 R 3 The anion exchange capacity of the epoxy resin in the form of is 20 μmol / mL-200 μmol / mL, preferably 20 μmol / mL, 30 μmol / mL, 40 μmol / mL, 50 μmol / mL, 60 μmol / mL, 70 μmol / mL, 80 μmol / mL, 90 μmol / mL, 100 μmol / mL, 110 μmol / mL, 120 μmol / mL, 130 μmol / mL, 140 μmol / mL, 150 μmol / mL, 160 μmol / mL, 170 μmol / mL, 180 μmol / mL, 190 μmol / mL, 200 μmol / mL; The pore size of the monolithic column is 2 μm-6 μm, preferably 2.0 μm, 2.1 μm, 2.2 μm, 2.3 μm, 2.4 μm, 2.5 μm, 2.6 μm, 2.7 μm, 2.8 μm, 2.9 μm, 3.0 μm, 3.1 μm, 3.2 μm, 3.3 μm, 3.4 μm, 3.5 μm, 3.6 μm, 3.7 μm, 3.8 μm , 3.9μm, 4.0μm, 4.1μm, 4.2μm, 4.3μm, 4.4μm, 4.5μm, 4.6μm, 4.7μm, 4.8μm, 4.9μm , 5.0μm, 5.1μm, 5.2μm, 5.3μm, 5.4μm, 5.5μm, 5.6μm, 5.7μm, 5.8μm, 5.9μm, 6.0μm; The pore volume of the monolithic column is 1.1 mL / g-1.8 mL / g, preferably 1.10 mL / g, 1.15 mL / g, 1.20 mL / g, 1.25 mL / g, 1.30 mL / g, 1.35 mL / g, 1.40 mL / g, 1.45 mL / g, 1.50 mL / g, 1.55 mL / g, 1.60 mL / g, 1.65 mL / g, 1.70 mL / g, 1.75 mL / g, 1.80 mL / g; The porosity of the integral column is 55%-68%, preferably 55.0%, 55.5%, 56.0%, 56.5%, 57.0%, 57.5%, 58.0%, 58.5%, 59.0%, 59.5%, 60.0%, 60.5%, 61.0%, 61.5%, 62.0%, 62.5%, 63.0%, 63.5%, 64.0%, 64.5%, 65.0%, 65.5%, 66.0%, 66.5%, 67.0%, 67.5%, 68.0%.
5. The integral column according to any one of claims 1 to 4, characterized in that: The raw materials of the monolithic column include a substance A containing multiple epoxy groups, a porogen B, and a quaternary ammonium salt modifier D; The quaternary ammonium salt modifier D has NR 1 R 2 R 3 exists in the form of; Among them, R 1 , R 2 , R 3 is an alkyl, alkenyl, alkynyl, cycloalkyl, heterocycloalkyl, poly(alkylene oxide) group, poly(alkylene amine) group, polyvinyl alcohol group, or polyvinyl amine group; wherein the alkyl, alkenyl, alkynyl, cycloalkyl, heterocycloalkyl, poly(alkylene oxide) group, poly(alkylene amine) group, polyvinyl alcohol group, or polyvinyl amine group is optionally substituted by an amino, hydroxyl, -C 1-6 Alkyl, -C 1-6 Hydroxyalkyl, -C 1-6 The aminoalkyl group is substituted or hybridized with O, N, Si, P, or S.
6. A method for preparing a monolithic column according to any one of claims 1 to 5, characterized in that: The steps include: S1. Hydroxylating the monolithic column; S2. Quaternizing the hydroxylated monolithic column.
7. The preparation method according to claim 6, characterized in that: The step S1 comprises: S13. Add an acidic aqueous solution into the dried monolithic column and heat the reaction to convert the residual epoxy groups in the monolithic column into hydroxyl groups.
8. The preparation method according to any one of claims 6 to 7, characterized in that: The step S2 comprises: S23. Adding a quaternary ammonium salt modifier D solution to the monolithic column, after sufficient infiltration, adding a catalyst, heating the reaction, so that the hydroxyl groups in the monolithic column are converted into quaternary ammonium salt groups; or S23. After mixing the quaternary ammonium salt modifier D solution with the catalyst, add the monolithic column and heat the reaction to convert the hydroxyl groups in the monolithic column into quaternary ammonium salt groups.
9. The preparation method according to claim 8, characterized in that: The catalyst is alkaline or acidic ammonium cerium nitrate; the alkaline is one or more of potassium hydroxide and sodium hydroxide; the acidic ammonium cerium nitrate is a mixture of cerium nitrate and acid, and the acid is one or more of sulfuric acid, hydrochloric acid, nitric acid, formic acid and acetic acid.
10. Use of the monolithic column according to any one of claims 1 to 5 or the monolithic column prepared by the preparation method according to any one of claims 6 to 9 for enrichment and separation of DNA or RNA.
11. A chromatographic column, characterized in that: It comprises the monolithic column as described in any one of claims 1 to 5 or the monolithic column prepared by the preparation method as described in any one of claims 6 to 9.
Citation Information
Patent Citations
Hydrophilic integral material as well as preparation and application thereof
CN113145088A
Chromatographic material raw material composition, chromatographic material, preparation method and application of chromatographic material, monolithic column and chromatographic pile
CN118179462A
Monolithic column having immobilized monomeric avidin for enriching and identifying biotinylated species
EP2485836A1
Cited By
Quaternary ammonium salt-modified strong anion-exchange monolithic column
WO2025232850A1